Penanda Referensi dalam Tajuk Rencana Surat Kabar Republika Edisi Februari 2017 dan Relevansinya sebagai Bahan Ajar Bahasa Indonesia di SMA Kelas XII - Siti Islamiyati, Idha, Dra. Atiqa Sabardila, M.Hum (2017)
The aim of the researchs are (1) describing reference marker form on editorial discourse in Republica newspaper on February, 2017 edition. (2) explaining reference relevancy on editorial discourse in Republica newspaper on February, 2017 edition as Bahasa Indonesia teaching materialin in class XII Senior High School. The type of the research uses descriptive qualitative research. The collecting data type uses library data analysis, reading technique, and recording technique. The data analysis presentation technique uses the method of agih and padan. The validity data in the research uses theory of triangulation. The outcomes of the research explain that first, reference marker form which has found are (a) the reference persona of 51 markers including the reference includes I persona reference saya, kita, -ku. II persona reference is anda pronominal. III persona references are -nya, dia, ia, beliau, dan mereka. (b) demonstratif references of 31 markers data including time demontrastive, they are for present (saat ini, hari ini, tahun ini), past (yang lalu, kemarin, yang akan datang, besok, mendatang, ke depan). While, place demonstrative reference tells about the object which closes to the speaker (ini) , the object which not too close to the speaker (itu), the object which is far from the speaker (sana) and describe explicitly which has mentioned in the discourse. (c) comparative references of 3 markers are seperti. Both of the research result can be used as Bahasa Indonesia teaching material, correlated it with Kompetensi Inti (KI) and Kompetensi Dasar (KD).